Legg-Calve-Perthes 병에서 나사를 이용한 대전자 골단유합술의 효과 - 김성수(Sung Soo Kim); 김현준(Hyeon Jun Kim); 정성윤(Sung Yoon Jung); 임철순(Chul Soon Im); 김동률(Dong Ryul Kim) (The journal of the Korean Orthopaedic Association, 2018)
목적: Legg-Calve-Perthes (LCP) 병에서 시행한 대전자 나사 골단유합술 후 대전자부의 성장판에 의한 길이 성장 및 부가 성장 두가지에 미치는 영향을 조사하였다. 대상 및 방법: 2003년 12월부터 2012년 12월까지 동아대학교병원에서 LCP 병으로 진단받고 대전자의 나사 골단유합술 및 추후 금속제거술까지 시행한 환자 중 4년 이상의 추시 관찰을 시행한 환자 17명을 대상으로 하였다. 골단유합술 시행 시, 금속제거술 시, 추시 관찰 시 전후면 방사선 사진을 이용하여 대퇴골 장축에 대하여 수직을 이루는 선 중에서 대퇴 골두와 가장 근위부가 만나는 선과대전자의 가장 근위 첨부를 지나는 선 간의 거리인 arctui lo-trochanter tip distance (ATD), 나사 경부에서 대전자의 첨부까지의 거리를 대퇴골 장축과 평행한 방향으로 측정한 거리인 trochanter tip-screw distance (TSD), 대전자 성장판의 원위부부터 대전자 첨부까지의 거리를 대퇴골 장축과 평행하게 측정한 거리인 trochanter tip-trochanter lower margin distance (TLD), 나사 경부에서 대전자성장판의 원위부까지 거리인 screw-trochanter lower margin distance (SLD)를 측정하였다. 결과: ATD는 환,건측에서 수술 전 평균 14.2 mm, 16.8 mm, 최종 추시관찰 시 평균 9.2 mm, 14.8 mm로 환측이 건측에 비해 감소하였다(p=0.030). 환측의 TLD는 나사 골단유합술 시 평균 30.8 mm에서 최종 추시 시 41.8 mm로 11.0 mm 증가하였고, 건측은 평균 26.7 mm에서 41.0 mm로 14.3 mm 증가하여 수술한 환측의 대전자 성장은 건측에 비해 76.7%였다.건측에 대한 환측의 TLD 비는 처음 1.15에서 금속제거술 시 1.02로 감소하였다(p=0.014). TSD는 나사 골단유합술 시 4.5 mm에서 금속제거술 시 14.4 mm로증가하였으며(p＜0.001) 최종 추시 시에는 17.0 mm로 측정되었다. TSD의 SLD에 대한 비도 나사 골단유합술 시 0.20에서 금속제거술 시 0.74로 증가하였으며(p＜0.001) 최종 0.84로 증가하였다. 결론: LCP 병에서 나사를 이용한 골단유합술은 대전자의 전체 성장은 억제할 수 있었고 부가 성장은 억제 못하였고 대전자과성장을억제 못하여 대전자 원위이전술이 필요하였다. 나사를 이용한 골단유합술은 대전자 성장 억제에 좋은 방법이 아닌 것로으 판단된다. Purpose: To evaluate the interstitial and appositional growth of greater trochanter post-screw apophysiodesis in Legg-Calve-Perthes (LCP) disease. Materials and Methods: A total of 17 patients, who were diagnosed with LCP and underwent greater trochanter screw apophysiodesis and metal removal between December 2003 and December 2012, and were followed-up for at least 4 years, were selected. Anterioposterior radiologic images were taken in each process of apophysiodesis, metal removal, and last follow-up. From such images, articulotrochanter tip distance (ATD), trochanter tip-screw distance (TSD), trochanter tip-trochanter lower margin distance (TLD), and screw-trochanter lower margin distance (SLD) were measured. Appositional growth and greater trochanter growth rates were compared using paired t-test, independent t-test, and correlation analysis. Results: The average ATD of the affected and unaffected sides was 14.2 and 16.8 mm, respectively at apophysiodesis and 9.2 and 14.8 mm at the last follow-up, with a significantly greater decrease observed on the affected side the unaffected side (p=0.030). TLD of the affected side during the follow-up increased 11.0 mm, from an average of 30.8 to 41.8 mm, while the un-affected side increased 14.3 mm, from an average of 26.7 to 41.0 mm. The growth of greater trochanter after the operation in the affected side was 76.7% of that in unaffected side. The ratio of TLD of the affected side to the unaffected side was significantly reduced, from 1.15 to 1.02 (p=0.014) at the final follow-up. TSD was significantly increased from 4.5 to 14.4 mm at metal removal (p＜0.001) and increased to 17.0 mm at the last follow-up. Moreover, the ratio of TSD to SLD was significantly increased from 0.20 to 0.74 at metal removal (p＜0.001) and increased to 0.84 at the final follow-up. Conclusion: The results of this study showed that screw apophysiodesis can suppress the overall growth, but not the appositional growth of the greater trochanter. Therefore, screw apophysiodesis may not be a good procedure to inhibit the growth of greater trochanter KCI Citation Count: 0